Penerapan Metode Ear Training Untuk Meningkatkan Kemampuan Bernyanyi Siswa Di MTsN 3 - Moh. Fikri Azhar; Jagar Lumbantoruan (EDUMUSIKA, 2024)
This research is based on the low singing ability of students who participate in extracurricular polyphonic choir activities. Therefore, it is hoped that the application of ear training as a teaching method can help improve students' singing abilities in choir. The problem posed in this study is whether using ear training can enhance students' singing abilities in the choir extracurricular at MTsN 3 Kota Padang. This study aims to understand, describe, and analyze the improvement in singing ability in extracurricular choir activities through the application of ear training for students at MTsN 3 Kota Padang. This research uses Classroom Action Research (CAR) which consists of two cycles. Each cycle includes planning, action, observation, and reflection phases. Data collection techniques are carried out through observation, interviews, documentation, and assessment. It showed that the ear training method successfully improved students' singing skills in choir extracurricular activities. Students' behavior also shows a positive change from being previously less enthusiastic, unmotivated, and passive to becoming more enthusiastic, excited, and active during the learning process using ear training.